1993
DOI: 10.1021/bi00095a007
|View full text |Cite
|
Sign up to set email alerts
|

Homodinuclear (Pt,Pt) and heterodinuclear (Ru,Pt) metal compounds as DNA-protein cross-linking agents: Potential suicide DNA lesions

Abstract: Homodinuclear (Pt,Pt) and heterodinuclear (Ru,Pt) metal compounds having the generalized formula M(a)NH2(CH)4NH2M(b) are shown to form specific DNA lesions which can efficiently cross-link proteins to DNA. In this study, the homodinuclear case is represented by M(a) = M(b) = [cis-Pt(Cl2)-(NH3)] and the heterodinuclear case is represented by M(a) = [cis-RuCl2(DMSO)3] and M(b) = [cis-PtCl2(NH3)]. Native and denaturing polyacrylamide gel electrophoresis was used to show the formation of ternary coordination compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…Reardon and Sancar (60) show that XPD is making intimate contact with a psoralen monoadduct. Similar studies have shown UvrB can also be cross-linked to psoralen (61)or bis-platinum adducts (62). This general approach, the development and validation of a structural model for other mammalian proteins, should be generally applicable where structural information exists for closely functional related bacterial, archaeal, or yeast proteins, which share significant protein structural motifs or a structural protein fold.…”
Section: Discussionmentioning
confidence: 91%
“…Reardon and Sancar (60) show that XPD is making intimate contact with a psoralen monoadduct. Similar studies have shown UvrB can also be cross-linked to psoralen (61)or bis-platinum adducts (62). This general approach, the development and validation of a structural model for other mammalian proteins, should be generally applicable where structural information exists for closely functional related bacterial, archaeal, or yeast proteins, which share significant protein structural motifs or a structural protein fold.…”
Section: Discussionmentioning
confidence: 91%
“…DPC levels increase dramatically upon exposure to a variety of physical or chemical agents, including UV light (4), ionizing radiation (5), ␤-propiolactone (6), aldehydes (1,(7)(8)(9), arsenite (10), ferric nitrilotriacetate (11), chromate (12), nickel (13), and others. Chemotherapeutic agents, such as cisplatin (12,14), bisplatinum (15), and neocarcinostatin (16), have also been shown to induce DPC formation. Exposure to several DPC-inducing agents gives rise to genotoxic and carcinogenic effects, and for some agents, such as formaldehyde, their primary mutagenic effects are believed to be mediated through the formation of DPCs (7,9).…”
mentioning
confidence: 99%
“…Molecular weight markers were also electrophoresed side by side: phosphorylase (M r ϭ 97,400), albumin (66,267), aldolase (42,400), carbonic anhydrase (30,000), trypsin inhibitor (20,100), and lysozyme (14,400). The gel was briefly stained with Coomassie Brilliant Blue (CBB), dried, and subjected to autoradiography.…”
Section: Methodsmentioning
confidence: 99%
“…Although Oxa and 2-deoxyribonolactone are base and sugar lesions, respectively, they have a lactone structure in common that is prone to react with nucleophilic molecules. cis-Platinum, which is known to form DPC and is used as a anticancer drug, also induces cross-links between DNA and UvrA/UvrB proteins involved in nucleotide excision repair (66). Thus, irreversible inhibition of repair enzymes by covalent trapping has a dual biological effect: DPC formation in general and suicide of DNA repair enzymes in particular.…”
Section: Dpc Formation Withmentioning
confidence: 99%